(untitled) (American Journal of Islam and Society, 2004)
The third Annual International Conference on Globalization for the Common Good was held on 27-31 March 2004 at the Bustan Rotana hotel, Dubai, the United Arab Emirates. More than thirty participants, representing academics, peace activists, theologians, environmentalists, and businessmen from the United States, Europe, Japan, the Gulf region, Australia, and South Africa attended the eleven plenary sessions. These were divided under the following headings: Muslim-Christian Dialogue for the Common Good; Religions and Social Justice; Profit and the Common Good: Conflict or Convergence?; Religions and the Common Good; Urbanization and Cities in a Global Age; Globalization and Civilizations; Ethical Perspectives on Globalization; Interfaith Dialogue and Peace-building; Natural Resources, Ecology and Development; Youth in a Global Age; and Science and Technology in a Global Age. The conference was officially opened by the founder and chief convenor of the Interfaith Perspective on Globalization for the Common Good, Dr Kamran Mofid of the United Kingdom. Dr William Lesher (Lutheran School of Theology, Chicago) in his “Pathways to Peace” identified the major factors supporting globalization and showed how global trends become indigenized through the process of glocalization. Sister Beatrice Mariotti’s (St. Mary’s Catholic High School, Dubai) “Globalization and Christian-Muslim Spiritual Dialogue in Dubai” dealt with three challenges to cultural identity: consumerism, the Internet, and isolationism. Markus Glatz-Schmallegger (Catholic Social Academy of Austria) argued in his “Religions Acting for ‘Bridging and Linking Social Capital’ in the Context of Globalization,” that religion, as an organ of civil society, can contribute significantly to social capital. In the session on “Profit and the Common Good: Conflict or Convergence?” Kamran Mofid outlined both the negative and positive aspects of globalization. This was followed by a lively discussion on how globalization’s benefits could be extended to all and not confined to a minority of individuals, multinationals, and states. Suleman Dangor (University of Kwazulu-Natal, South Africa) outlined the positive and negative features of globalization, and then elaborated on the role that religions could play in ensuring that its benefits are spread equitably while developing nations are protected from its negative impact. Jakob von Uexkull (The Right Livelihood Awards, London, UK), in his “Global Values and Global Stability,” made a case for equitable access to the world’s natural resources. The possibility of this happening is greater now that we are moving to a post-secular world. Keyvan Tabari emphasized the importance of national sovereignty. Since the demise of the USSR ...